The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1210/endocr/bqaa009
|View full text |Cite
|
Sign up to set email alerts
|

Protein Profile Changes in Circulating Placental Extracellular Vesicles in Term and Preterm Births: A Longitudinal Study

Abstract: Spontaneous preterm birth (PTB) is a major obstetrical problem around the globe and the mechanisms leading to PTB are unclear. Recently, changes in the circulating levels of placental extracellular vesicles (EVs) during pregnancy have been associated with various pregnancy complications. However, progress in the field is hindered by the inability to isolate placental EVs from the maternal circulation. A longitudinal study design was used to determine the protein cargo present in circulating placental EVs in ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 63 publications
3
50
2
Order By: Relevance
“…Identification of miRNAs transported by EVs also revealed potential biomarkers for the prediction of pre-term birth [98]. Changes of the protein composition of circulating placental EVs could also be used for the identification of a high-risk status for pre-term birth across gestation [99]. Ninety-six proteins were expressed at significantly different levels, and a bioinformatics analysis revealed their connection to inflammatory pathways, epithelial mesenchymal transition, and coagulation/complement activation.…”
Section: Pre-tterm Birthmentioning
confidence: 99%
“…Identification of miRNAs transported by EVs also revealed potential biomarkers for the prediction of pre-term birth [98]. Changes of the protein composition of circulating placental EVs could also be used for the identification of a high-risk status for pre-term birth across gestation [99]. Ninety-six proteins were expressed at significantly different levels, and a bioinformatics analysis revealed their connection to inflammatory pathways, epithelial mesenchymal transition, and coagulation/complement activation.…”
Section: Pre-tterm Birthmentioning
confidence: 99%
“…In this regard, Menon and colleagues have analyzed placental EVs during pregnancy and at delivery, and found that samples at term associated a group of upregulated genes known to be regulators of epithelial mesenchymal transition (EMT). They hypothesized that, when approaching term, fetal components of the placenta undergo EMT, which leads to an increase in mesenchymal cells susceptible to oxidative stress followed by subsequent inflammation that precipitates delivery [ 112 , 113 ]. Moreover, as a response to increased oxidative stress, it has been demonstrated that phosphorylation of p38 mitogen-activated protein kinase (MAPK), an indicator of term parturition, takes place in amniotic epithelial cell (AEC)-derived exosomes [ 114 ].…”
Section: Extracellular Vesicles In Normal Pregnancymentioning
confidence: 99%
“…Therefore, profiling their quantitative and intraexosomal cargoes may reflect conditional stress imposed on the placenta, and possibly on the fetus. In this context, several placental specific proteins have been studied, especially placental alkaline phosphatase (PLAP), syncytin-1, and syncytin-2 [1,[41][42][43][44][45][46][47]. These STEVs are released directly into the maternal circulation, where they may influence the surrounding tissue or may have systemic effects.…”
Section: Introductionmentioning
confidence: 99%